2014
DOI: 10.1037/law0000023
|View full text |Cite
|
Sign up to set email alerts
|

Police perceptions and contact among people with mental illnesses: Comparisons with a general population survey.

Abstract: Though studies have surveyed police officers’ perceptions of people with mental illnesses (PMI), few have examined perceptions held by PMI regarding the police, and none have compared them with those held by the general population. This study sought to (a) examine perceptions of police held by PMI, (b) compare them to perceptions held by the general population, and (c) explore whether differences between PMI and general population perceptions are attributable to contact with the police in the past year. We dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
(100 reference statements)
1
21
0
Order By: Relevance
“…Much has been reported about workplace stress (Alexopoulos et al 2014;Kotera et al 2018a;Morash et al 2006;Violanti et al 2016), and in regard to policing, a variety of research within the last 20 years has focussed on law enforcement's perception of mental health in the community (Desmarais et al 2014;Lamb et al 2002;Soomro and Yanos 2018;Watson et al 2014;Wood et al 2017); however, the occupational psychological distress of police officers has received little attention in the research literature. Frequent exposure to operational stressors has the potential to significantly affect the psychological functioning of police officers (Marchand et al 2015).…”
mentioning
confidence: 99%
“…Much has been reported about workplace stress (Alexopoulos et al 2014;Kotera et al 2018a;Morash et al 2006;Violanti et al 2016), and in regard to policing, a variety of research within the last 20 years has focussed on law enforcement's perception of mental health in the community (Desmarais et al 2014;Lamb et al 2002;Soomro and Yanos 2018;Watson et al 2014;Wood et al 2017); however, the occupational psychological distress of police officers has received little attention in the research literature. Frequent exposure to operational stressors has the potential to significantly affect the psychological functioning of police officers (Marchand et al 2015).…”
mentioning
confidence: 99%
“…For example, Wales, Hiday, and Ray (2010) found that procedurally just treatment from the judge in mental health court proceedings was associated with a positive appraisal of the process and a reduced risk of recidivism. More recent research has extended this procedural justice lens more specifically to considering encounters between the police and people experiencing mental illness, with some recent international research reporting that when people experiencing mental illness feel they have been treated in a procedurally just way they are likely to perceive the encounter as positive and to co-operate with police officers (Livingstone, Desmarais, Verdun-Jones et al 2014;Watson & Angell, 2013;Watson, Angell, et al, 2008).…”
Section: Procedural Justice Theorymentioning
confidence: 99%
“…Given the topicality of police encounters with people experiencing mental illness, it is perhaps surprising that only seven international published studies to date have looked at their views of encounters with police and overall attitudes to the police (Desmarais et al, 2014;Jones & Mason, 2002;Livingstone, Desmarais, Verdun-Jones et al, 2014;Livingstone, Desmarais, Greaves et al 2014;Watson & Angell, 2013;Watson, Angell, et al, 2008;Watson et al, 2010). This literature suggests that people experiencing mental illness have a largely negative perception of police officers and overall are dissatisfied with their encounters with the police (Desmarais et al, 2014). The importance of fair treatment from police officers emerged as a key theme from all seven studies.…”
Section: Perspectives Of Police Encounters By People Experiencing Menmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study, individuals suffering from mental health-related illnesses who were recently in contact with officers reported that when the officers treated them with fairness and respect, they were more willing to cooperate with the officer's orders rather than resist (Watson &Angell, 2013). These new approaches to responding to these types of calls for service are leading to fewer arrests and more supplemental services being provided (Desmarais, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%